Awareness and Perceptions on Bioethical Issues among Pre-Service Science Teachers - Zulkefli Daud; Zainab Ari; Noorafizah Daud (Bangladesh Journal of Bioethics)
This study aims to investigate the awareness and perception level of bioethical issues among pre-service science teachers at one of the Malaysian Education Institutions. A total of 67 respondents studying science major and science elective were involved. A questionnaire based survey with an alpha Cronbach of approximately 0.93 was used. Data were analysed using SPSS version 22. The results showed that the average awareness and perception level were